RESTRUCTURING OF BANK DEBT IN THE CONTEXT OF PKPU APPLICATIONS AS A MEANS TO SAVE BUSINESS ACTORS? - Rahmadi, Raendhi; Suryadi, Djaka (SUPREMASI HUKUM, 2024)
Postponing Debt Payment Obligations (PKPU) aims to achieve peace between customers and financing providers so that they can reach an agreement regarding how these debts will be paid. Financing restructuring is an effort to improve the activity of providing relief for paying financing debt installments to customers who may have difficulty fulfilling their obligations. The financing provided by sharia banking is always subject to the risk of payment failure, which creates financing issues. The efforts of Sharia banking to surmount non-implementation of financing are, in principle, identical to those of conventional banking. These efforts include restructuring financing, collateral execution, litigation, the national sharia arbitration council, writing off books, and returning debts by reducing principal debt. Keywords: Sharia Bank, Restructuring of Financing, and Non-Financing Performance